Egyetemi múzeumok és gyűjtemények Magyarországon, avagy sajátos helyzetű gyűjtemények bemutatása - Szilágyi, Judit (Per Aspera ad Astra, 2016)
The history and relevance of those museums and collections – owned and maintained by institutions of higher education – leads back to the establishment of the first universities. However, for the last 3 decades, interest in them shows a tendency towards revivalism. The reason for the new attention to university museums can be found in inevitable changes in society and education, as well as in the new tendency for the appreciation of the past and heritage. The goal of this article is to lay down the important principles and knowledge about university museums in general and in Hungary specifically. It can contribute to a Hungarian professional discourse since that has not developed as yet. Thus I describe those fundamental differences that essentially define university museums and collections, such as the complicated and often problematic ownership of these entities and the different target audience that originates from the basic roles namely the apparent focus to teaching and research. Referring to a survey that had been made between 2007–2011 I list the university museums and collections in Hungary by their registration, but I also found it important to introduce those collections and exhibitions which had not yet been registered. Furthermore I focus on the academic festive occasions, which nourishes the preservation and presentation of the heritage, and which later on can promote the establishment or further maintenance of these unregistered and thus „outlaw” exhibitions and collections.